Adding an Online Community to an Internet-Mediated Walking Program. Part 2: Strategies for Encouraging Community Participation - Resnick, Paul J; Janney, Adrienne W; Buis, Lorraine R; Richardson, Caroline R (JMIR Publications, 2010)
Starting a new online community with a limited number of members who have not self-selected for participation in the community is challenging. The space must appear active to lure visitors to return; when the pool of participants is small, a large fraction must be converted from lurkers to contributors, and contributors must receive responses quickly to encourage continued participation. We report on strategies for overcoming these challenges and our experience implementing them within an online community add-on to an existing Internet-mediated walking program.